Community resourcefulness and partnerships in rural tourism. Issue 10 (9th August 2022) - Qu, Meng; McCormick, A. D.; Funck, Carolin
Abstract: Small enterprises play a vital role in the drive toward sustainable tourism and in the sector more broadly, and their importance is accentuated in rural contexts. Beyond entrepreneurial spirit, what are the critical success factors that allow them to flourish? This study links tourism entrepreneurship, rural development and multi-stakeholder partnerships to situate community resourcefulness as a key plank in the sustainable tourism discourse. The focus of this study is six islands that play host to the Setouchi Triennale, a large art tourism initiative in rural Japan organized to revitalize declining regions. Highly divergent outcomes between communities emerged, directing attention toward community resourcefulness, where collective action leverages agency and capacity to effect change from within. Findings show the emergence of "art businesses", local social enterprises that function as both tourism and community assets and model sustainable development outcomes. Islands supporting such ventures reaped substantial community benefits, while islands without them struggled, their nascent tourism economies benefiting only tourists and commuter entrepreneurs. This study reveals the potential and the limitations of large-scale, multi-stakeholder tourism development initiatives that promote entrepreneurship in resource-constrained areas and highlights that community resourcefulness is the determining factor behind the success or failure in otherwise comparable communities.